Synthesis of Neoglycoconjugates Containing 4-Amino-4-deoxy-l-arabinose Epitopes Corresponding to the Inner Core of Burkholderia and Proteus Lipopolysaccharides - Blaukopf, Markus (WILEY-VCH Verlag, 2012)
Disaccharides that contain 3-deoxy-d-manno-oct-2-ulosonic acid (Kdo) and d-glycero-d-talo-oct-2-ulosonic acid (Ko) substituted at the 8-position by 4-amino-4-deoxy-β-l-arabinopyranosyl (Ara4N) residues have been prepared. Coupling an N-phenyltrifluoroacetimidate-4-azido-4-deoxy-l-arabinosylglycosyl donor to acetyl-protected allyl glycosides of Kdo and Ko afforded anomeric mixtures of disaccharide products in 74 and 90 % yield, respectively, which were separated by chromatography. Further extension of an intermediate Ara4N-(1→8)-Kdo disaccharide acceptor, which capitalized on a regioselective glycosylation with a Kdo bromide donor under Helferich conditions, afforded the branched trisaccharide α-Kdo-(2→4)[β-l-Ara4N-(1→8)]-α-Kdo derivative. Deprotection of the protected di- and trisaccharide allyl glycosides was accomplished by TiCl(4)-promoted benzyl ether cleavage followed by the removal of ester groups and reduction of the azido group with thiol or Staudinger reagents, respectively. The reaction of the anomeric allyl group with 1,3-propanedithiol under radical conditions afforded the thioether-bridged spacer glycosides, which were efficiently coupled to maleimide-activated bovine serum albumin. The neoglycoconjugates serve as immunoreagents with specificity for inner core epitopes of Burkholderia and Proteus lipopolysaccharides.